2017
DOI: 10.1093/ntr/ntx265
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the Predictive Validity of the Susceptibility to Smoking Construct for Tobacco Cigarettes, Alternative Tobacco Products, and E-Cigarettes

Abstract: This study presents the predictive validity of the susceptibility construct for the use of tobacco cigarettes among secondary school students in Ontario, Canada. It also presents a novel use of the susceptibility construct for predicting the use of e-cigarettes, cigarillos or little cigars, cigars, hookah, and smokeless tobacco among secondary school students in Ontario, Canada.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
56
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 50 publications
(62 citation statements)
references
References 30 publications
6
56
0
Order By: Relevance
“…Cole et al 31 measured the predictive validity of the Pierce et al three-item scale for cigarettes and non-cigarette tobacco products among a sample of high school students in Canada. They found that the sensitivity and specificity for the measure were still highest for cigarettes 31 .…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Cole et al 31 measured the predictive validity of the Pierce et al three-item scale for cigarettes and non-cigarette tobacco products among a sample of high school students in Canada. They found that the sensitivity and specificity for the measure were still highest for cigarettes 31 .…”
Section: Discussionmentioning
confidence: 99%
“…Cole et al 31 measured the predictive validity of the Pierce et al three-item scale for cigarettes and non-cigarette tobacco products among a sample of high school students in Canada. They found that the sensitivity and specificity for the measure were still highest for cigarettes 31 . When comparing these values to those from our study, they show similar patterns, though our study measures participants' ever use of the product, whereas Cole et al 31 measured participants' current use of the product.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations